Colour as a tool of leading users to particular actions on websites - Tudoran, Viktoriya (Видавництво Львівської політехніки, 2016)
The issue of leading users to making partucular actions by pressing specified buttons on websites is discussed. On the base of visual flow theory and researching of two types of online services in english, german, polish and russian languages the optimal parameters of action buttons were defined.
Keywords: website; online shops; classifieds services; human-computer interface; visual flow; focus point; action button; leading of users; usability; colour